Pharmacological inhibition of AKT activity in human CD34(+) cells enhances their ability to engraft immunodeficient mice - Chen, Sisi (Exp Hematol, 2016)
Although practiced clinically for more than 40 years, the use of hematopoietic stem cell (HSC) transplantation remains limited by the inability to expand functional HSCs ex vivo. To determine the role of phosphoinositide 3-kinase (PI3K)/AKT signaling in human hematopoietic stem and progenitor cell (HSPC) maintenance, we examined the effect of genetic and pharmacological inhibition of AKT on human umbilical cord blood (UCB) CD34(+) cells. We found that knock-down of AKT1 in human UCB CD34(+) cells using short interfering RNAs targeting AKT1 enhances their quiescence and colony formation potential in vitro. We treated human UCB CD34(+) cells with an AKT-specific inhibitor (AKTi) and performed both in vitro and in vivo stem and progenitor cell assays. We found that ex vivo treatment of human HSPCs maintains CD34 expression and enhances colony formation in serial replating assays. Moreover, pharmacological inhibition of AKT enhances the short-term repopulating potential of human UCB CD34(+) cells in immunodeficient mice. Mechanistically, genetic and pharmacological inhibition of AKT activity promotes human HSPC quiescence. These preclinical results suggest a positive role for AKTi during ex vivo culture of human UCB HSPCs.